1995
DOI: 10.1073/pnas.92.20.9077
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activation of NF-kappa B by glutamate in cerebellar granule neurons in vitro.

Abstract: Neuronal proliferation, migration, and differentiation are regulated by the sequential expression of particular genes at specific stages of development. Such processes rely on differential gene expression modulated through second-messenger systems. Early postnatal mouse cerebellar granule cells migrate into the internal granular layer and acquire differentiated properties. The neurotransmitter glutamate has been shown to play an important role in this developmental process. We show here by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
2
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(183 citation statements)
references
References 27 publications
12
164
2
5
Order By: Relevance
“…In post-mortem tissue from patients with neurodegenerative disease or cultured Expression profiling of NMDA receptor antagonists in brain M Marvanová et al neurons exposed to neurotoxic stimuli, increased NF-kB activity in cells has been reported (Kaltschmidt et al, 1995;Terai et al, 1996;Hunot et al, 1997). Furthermore, several studies have demonstrated that stimulation of both NMDA and non-NMDA glutamate receptors strongly stimulate NF-kB in vitro (Guerrini et al, 1995;Kaltschmidt et al, 1995). Additionally, another gene involved in immune and inflammatory responses, prostaglandin EP2 receptor (Narumiya et al, 1999), was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In post-mortem tissue from patients with neurodegenerative disease or cultured Expression profiling of NMDA receptor antagonists in brain M Marvanová et al neurons exposed to neurotoxic stimuli, increased NF-kB activity in cells has been reported (Kaltschmidt et al, 1995;Terai et al, 1996;Hunot et al, 1997). Furthermore, several studies have demonstrated that stimulation of both NMDA and non-NMDA glutamate receptors strongly stimulate NF-kB in vitro (Guerrini et al, 1995;Kaltschmidt et al, 1995). Additionally, another gene involved in immune and inflammatory responses, prostaglandin EP2 receptor (Narumiya et al, 1999), was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, the most common NF-kB complex appears to consist of p65, p50 and IkBa. [2][3][4][5] However, other complexes are present in neurons and their subunit composition may vary depending upon factors such as the developmental state of the neurons and their location within the nervous system. 6,7 The canonical mechanism of NF-kB activation involves phosphorylation of the inhibitory IkB subunit by the IkB kinase complex (IKK); 8 phosphorylation targets IkB for ubiquitination and subsequent proteasomal degradation, thereby releasing the active NF-kB factor dimer ( Figure 1).…”
Section: The Basics Activation Of Nf-jb In Neuronsmentioning
confidence: 99%
“…A growing list of signals that can activate NF-kB in neurons includes tumor necrosis factor-a (TNF), 9 the excitatory neurotransmitter glutamate, 3 nerve growth factor (NGF), 10,11 activity-dependent neurotrophic factor (ADNF), 12 a secreted form of amyloid precursor protein 13 and cell adhesion molecules. 14 These molecules can activate NF-kB through coupling to kinase cascades including calcium/calmodulindependent kinase II, 15 Akt 16,17 and protein kinase C 18 ( Figure 2).…”
Section: The Basics Activation Of Nf-jb In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has been found that stimulation of glutamate receptors after excitatory amino acids (EAAs) released during stress leads to the activation of NF-kB in neurons (Guerrini et al, 1995;Kaltschmidt et al, 1995), we decided to explore this possibility. The NMDA receptor blocker MK-801 (0.2 mg/kg) decreases both stress-induced PGE 2 accumulation and COX-2 expression (Figure 3a and b, respectively).…”
Section: Mechanisms Of Cox-2 Expression In Stressmentioning
confidence: 99%